Structural analysis of methyl 6-O-benzyl-2-deoxy-2-dimethylmaleimido- α-D-allopyranoside by X-ray crystallography, NMR, and QM calculations: Hydrogen bonding and comparison of density functionals - Colombo, María Inés (2012)
The crystal structure of methyl 6-O-benzyl-2-deoxy-2-dimethylmaleimido- α-d-allopyranoside was solved in order to gain insight into the hydrogen bond features which can be determining features in the glycosylation regioselectivity observed for this compound. An intramolecular hydrogen bond between the hydroxyl H(O)3 and a carbonyl oxygen from the dimethylmaleoyl (DMM) group was observed. This was in agreement with previous NMR temperature shift determinations and molecular modeling. The determination has also found an intermolecular hydrogen bond between the second hydroxyl H(O)4 and the other carbonyl oxygen (generated by symmetry) from DMM. The crystal structure was optimized by five different functionals, namely the hybrid methods B3LYP, M06-2X, B3PW91, and PBE0, and the pure functional PBE, and the optimized geometries were compared with the crystal geometry and with MM3. An excellent coincidence of the geometries was found with the five quantum methods, with minor details deviating from this coincidence. PBE tends to yield larger bond distances, whereas M06-2X fails slightly to match the exocyclic torsion angles for the sugar moiety. In any case, the differences are small, implying that any of these functionals can accurately emulate the geometries of a complex carbohydrate derivative like this one.